2013
DOI: 10.1063/1.4798270
|View full text |Cite
|
Sign up to set email alerts
|

Impact ionisation electroluminescence in planar GaAs-based heterostructure Gunn diodes: Spatial distribution and impact of doping non-uniformities

Abstract: (2013) Impact ionisation electroluminescence in planar GaAs-based heterostructure gunn diodes: spatial distribution and impact of doping non-uniformities. Journal of Applied Physics, 113 (12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…First, the electronic band structure of some semiconductor materials such GaAs has another energy sub-band in addition to valence band and conduction band. 17 This third band is at a higher energy than the normal conduction band and is empty until a sufficient energy is supplied to promote electrons to it. Meanwhile, the mobility or drift velocity in the third band is lower than that in the usual conduction band.…”
mentioning
confidence: 99%
“…First, the electronic band structure of some semiconductor materials such GaAs has another energy sub-band in addition to valence band and conduction band. 17 This third band is at a higher energy than the normal conduction band and is empty until a sufficient energy is supplied to promote electrons to it. Meanwhile, the mobility or drift velocity in the third band is lower than that in the usual conduction band.…”
mentioning
confidence: 99%
“…An ensemble Monte Carlo method was used to simulate the carrier transport in the studied devices with an established 2-D Ensemble Monte Carlo (EMC) transport model, details of Investigation of contact edge effects in the channel of planar Gunn diodes A Mindil, G M Dunn, A Khalid, and C H Oxley P which are given in [10], which has been validated against many similar experimentally realized devices [1][2][3][4][5][6][7][8][9][10]. As in [11] a doping notch next to the cathode contact was used to simulate the effect of the cathode contact to precipitate domain formation.…”
Section: Device Simulationmentioning
confidence: 99%
“…This suggests high electric fields exist, particularly where we might expect such fields, at the sharp corner of the electrical contacts. In a previous study [9] it was found that geometrical modifications to the anode contact along its length could reduce the effect along its length, but had little effect on the high electric fields at the corners of the anode contact. In this present work, using Monte Carlo simulations, we will look at the effect of the corner of the anode contact on the progress of Gunn domains and at the effect of shaping the contacts to restore consistent domain wave-front across the width of the channel from cathode to anode.…”
Section: Introductionmentioning
confidence: 98%
“…These include: (1) current saturation arising from velocity overshoot [4]- [6]; (2) strongly-enhanced noise (and self-sustained current oscillations) induced by high-field domains [1], [3], [17], [18] and; (3) Electro-luminescence (EL) due to recombination of electrons and holes created by impact ionization within the domains [17], [19]- [22]. We demonstrate all of these features in the operation of GaAs-based NCs, thereby providing strong evidence that the Gunn effect may indeed be induced in such structures.…”
Section: Introductionmentioning
confidence: 99%